The Smc5/6 Complex Is an ATP-Dependent Intermolecular DNA Linker - Takaharu Kanno; Davide G. Berta; Camilla Sjögren (Cell Reports, 2015)
The structural maintenance of chromosome (SMC) protein complexes cohesin and condensin and the Smc5/6 complex (Smc5/6) are crucial for chromosome dynamics and stability. All contain essential ATPase domains, and cohesin and condensin interact with chromosomes through topological entrapment of DNA. However, how Smc5/6 binds DNA and chromosomes has remained largely unknown. Here, we show that purified Smc5/6 binds DNA through a mechanism that requires ATP hydrolysis by the complex and circular DNA to be established. This also promotes topoisomerase 2-dependent catenation of plasmids, suggesting that Smc5/6 interconnects two DNA molecules using ATP-regulated topological entrapment of DNA, similar to cohesin. We also show that a complex containing an Smc6 mutant that is defective in ATP binding fails to interact with DNA and chromosomes and leads to cell death with concomitant accumulation of DNA damage when overexpressed. Taken together, these results indicate that Smc5/6 executes its cellular functions through ATP-regulated intermolecular DNA linking.